Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.1371/journal.pone.0015397
|View full text |Cite
|
Sign up to set email alerts
|

An Essential Role of the Cytoplasmic Tail of CXCR4 in G-Protein Signaling and Organogenesis

Abstract: CXCR4 regulates cell proliferation, enhances cell survival and induces chemotaxis, yet molecular mechanisms underlying its signaling remain elusive. Like all other G-protein coupled receptors (GPCRs), CXCR4 delivers signals through G-protein-dependent and -independent pathways, the latter involving its serine-rich cytoplasmic tail. To evaluate the signaling and biological contribution of this G-protein-independent pathway, we generated mutant mice that express cytoplasmic tail-truncated CXCR4 (ΔT) by a gene kn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 52 publications
(50 reference statements)
1
18
0
Order By: Relevance
“…Using in ovo electroporation, we expressed in pharyngeal NCs either a miRNA against Cxcr4 (miRNA-Cxcr4, Fig. S5) or a dominant-negative form of Cxcr4 (DN-CXCR4) lacking the C-terminus sequences necessary for chemotactic migration (Ahr et al, 2005;Cronshaw et al, 2010). First, we searched for craniofacial dysmorphogenesis due to palate and jaw anomalies, a prominent trait of DGS patients (Fukui et al, 2000;Karpinski et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…Using in ovo electroporation, we expressed in pharyngeal NCs either a miRNA against Cxcr4 (miRNA-Cxcr4, Fig. S5) or a dominant-negative form of Cxcr4 (DN-CXCR4) lacking the C-terminus sequences necessary for chemotactic migration (Ahr et al, 2005;Cronshaw et al, 2010). First, we searched for craniofacial dysmorphogenesis due to palate and jaw anomalies, a prominent trait of DGS patients (Fukui et al, 2000;Karpinski et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…7,8 However, the complete deletion of the Cxcr4 C-tail leads to a loss of G protein-dependent function that causes developmental defects similar to those of Cxcr4-null mice. 19 This suggests that the remaining residues in the C-tail of WS-associated CXCR4 mutants that are targeted by numerous regulators 8,9,18 contribute to the enhanced CXCL12-dependent signaling. In lysates from WT mice, Cxcr4 ϩ/1013 mice, and Cxcr4 1013/1013 mice obtained by intercrossing heterozygous mice, immunodetection of Cxcr4 similarly revealed 1 band, suggesting that mutant and WT receptors cannot be distinguished in size (supplemental Figure 1D).…”
Section: Cxcr4 ؉/1013 Leukocytes Exhibit a Gain Of Cxcr4 Functionmentioning
confidence: 99%
“…Because SDF1 signaling is known to regulate both chemotactic migration and cell survival, 19 we overexpressed a construct encoding a dominant-negative form of Cxcr4 (DN-Cxcr4), in which the C-tail of the molecule was deleted. CXCR4 C-tail has been shown to be dispensable for SDF1-dependent survival but critical for chemotaxis, 20,21 allowing it to discriminate between SDF1 activities during cardiac NC migration. HNK1 immunolabeling revealed that 15 hpe, NCs expressing the DN-Cxcr4 were lagging behind the nonelectroporated NCs ( Figure 4A and 4B).…”
Section: Loss Of Cxcr4 Signaling Leads To Defective Cardiac Nc Migrationmentioning
confidence: 99%
“…It has been suggested that CXCR4 is involved in chemotaxis and CXCR7 in survival, 24 but other studies also proposed that both processes may be controlled by CXCR4. 25 In addition, biochemical studies showed that the CXCR4 C-terminal-tail is dispensable for activation of the Jak2/ STAT3 pathway involved in SDF1-dependent survival 20 or for integrin-mediated adhesion, 21 but is critical for chemotaxis. 20 Our results show that CXCR4, but not CXCR7, is expressed in cardiac NCs during their initial migration and that CXCR4 downregulation by miRNA leads to their apoptosis, whereas a dominant-negative form of CXCR4 lacking its C-terminal domain induces their misrouting without causing cell death, arguing for a role of CXCR4 in controlling both events in cardiac NCs.…”
Section: Sdf1 Drives Cardiac Nc Migration and Survival Through The CXmentioning
confidence: 99%